Ion source and Model 105-G3 Magnetic Electron Multiplier - Bendix Corporation (1959)
Two views of an ion source and Model 105-G3 Magnetic Electron Multiplier designed for use with the Bendix Corporation Time-of-Flight Mass Spectrometer. One of four component parts of a mass spectrometer, the ion source produces a beam of particles characteristic of the sample material for qualitative and quantitative analysis, while the magnetic electron multiplier is used to detect and amplify ion bunches or peaks.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers